STUDY OF POLICY IN THE EFFORT TO HANDLE THE PROBLEMS OF THE COVID-19 PANDEMI FOR VULNERABLE INDIVIDUALS (CHILDREN, ELDERLY, AND DISABLED) IN ADI REJO VILLAGE, EAST LAMPUNG REGENCY - Yuditya Wardhana (LPM Universitas Pasundan, 2021)
During the COVID-19 pandemic in Indonesia, the central and regional governments have issued a series of policy packages in handling the disease outbreak. The current pandemic situation has become extraordinary due to several aspects. First, this situation has a long-lasting impact on the health, mental, economic and social conditions of the community. Second, the handling of COVID-19 will not be effective in alleviating the suffering of the affected community, especially for vulnerable individuals (children, elderly, and disabled) if without adequate implementation arrangements. Third, Indonesia has almost no experience in dealing with pandemic situations of this scale. The goal to be achieved in this community service activity is as a form of introducing and providing understanding to the public about policy studies in overcoming COVID-19 problems in vulnerable individuals. The service activity was carried out on Thursday, August 5, 2021 in Adi Rejo Village, East Lampung Regency. This activity took place in the form of socialization and discussion with the community and local village officials. The result of this activity is the achievement of goals and benefits in community service activities. Keywords: Public Policy, COVID-19 Pandemic, Vulnerable Individuals.